Assessment of Important Trees Outside forests (TOF) in Gorakhpur District of Uttar Pradesh - Srivastav, Anubha; Pandey, A. K.; Dubey, Ritesh (Indian Forester, 2012)
A study has been undertaken to assess the number of six important tree species including teak (Tectona grandis), mango (Mangifera indica), babool (Acacia nilotica), neem (Azadirachta indica), kathal (Artocarpus heterophyllus) and shisham (Dalbergia sissoo) outside forests in rural areas of district Gorakhpur. Out of 3327 villages of Gorakhpur district, 66 villages (2%) were taken for the study. Number of trees on the basis of diameter classes was recorded in selected villages of respective tehsils. A total of 6,71,852 trees of teak, 4,83,876 trees of mango, 99,053 trees of neem, 36748 trees of kathal, 2,88,995 trees of shisham and 68,909 trees of babool were enumerated in different diameter classes. It was found that babool and kathal trees were very less as compared to other species. Thus, introduction of these species in large areas/private land of farmers may be a viable option for minimizing demand-supply gap as well as to increase the tree cover.